Strategi Pengembangan Sumber Daya Manusia Koperasi Merah Putih Indonesia - Fifian Permata Sari; Munajat Munajat (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to analyze the internal and external factors of the Merah Putih Cooperative and formulate strategies that can be recommended for human resource development at the Merah Putih Cooperative in South Sumatra Province, Indonesia. Research Methodology: The method used in this study is a case study method, where OKU Regency is used as a sample case of the Merah Putih Cooperative in South Sumatra Province, Indonesia. The sampling method used was a census, in which all 157 members of the Merah Putih Cooperative were taken as research samples in July 2025.  The analysis used in this study was SWOT analysis. Results: The results of the SWOT analysis in Quadrant I show that the strategies that can be recommended for human resource development at the Merah Putih Cooperative include strengthening human resources and institutions, developing businesses based on local economic potential, increasing human resource capacity, and strengthening business partnerships to encourage the sustainability and competitiveness of the cooperative. Conclusions: The Merah Putih Cooperative is positioned in SWOT Quadrant I, indicating strong internal and external conditions to support human resource development. Recommended strategies focus on strengthening human resources and institutions, utilizing local economic potential, and reinforcing business partnerships to enhance sustainability and competitiveness. Limitations: This study is limited to a single cooperative case in OKU Regency, which may limit the generalizability of the findings. The SWOT approach also does not quantify the impact of each proposed strategy. Contribution: This study provides practical insights for cooperative managers and policymakers in formulating human resource development strategies for rural cooperatives, particularly in supporting village-based economic development in Indonesia.